Myomectomy at time of cesarean delivery: a retrospective cohort study - Tabsh Khalil MA; Roman Ashley S (BMC, 2004)
Abstract Background Myomectomy at time of cesarean delivery is traditionally discouraged because of the risk of hemorrhage. A retrospective cohort study was performed to determine whether myomectomy at time of cesarean delivery leads to an increased incidence of intrapartum and short-term postpartum complications. Methods A computer search of medical records from May 1991 to April 2001 identified a total of 111 women who underwent myomectomy at time of cesarean delivery and 257 women with documented fibroids during the index pregnancy who underwent cesarean delivery alone. Charts were reviewed for the following outcome variables: change in hematocrit from preoperative to postoperative period, length of operation, length of postpartum stay, incidence of postpartum fever, and incidence of hemorrhage. Hemorrhage was defined as a change in hematocrit of 10 points or the need for intraoperative blood transfusion. Results The incidence of hemorrhage in the study group was 12.6% as compared with 12.8% in the control group (p = 0.95). There was also no statistically significant increase in the incidence of postpartum fever, operating time, and length of postpartum stay. No patient in either group required hysterectomy or embolization. Size of fibroid did not appear to affect the incidence of hemorrhage. After stratifying the procedures by type of fibroid removed, intramural myomectomy was found to be associated with a 21.2% incidence of hemorrhage compared with 12.8% in the control group, but this difference was not statistically significant (p = 0.08). This study had 80% power to detect a two-fold increase in the overall incidence of hemorrhage. Conclusion In selected patients, myomectomy during cesarean delivery does not appear to result in an increased risk of intrapartum or short-term postpartum morbidity.